Relação da expressão do tlr-2, da enzima iNOS, das citocinas IL-10, TNF-α e TGF-β com a carga parasitária da pele de cães naturalmente acometidos por leishmaniose visceral: Dandara Camila Morais Pereira. - - Pereira, Dandara Camila Morais [UNESP] (2015)
The progression of the canine visceral leishmaniasis (CVL) is related to the immune response profile. The effective cellular immunity is related to the predominance of Th1 cytokines such as TNF-α and the disease is related to an exacerbated humoral immune response, with the predominance of Th2 cytokines such as IL-10 and TGF-β. TLR-2 is an important receptor of the innate immunity involved in the induction of the cytokines production and the activation of iNOS in visceral leishmaniasis. To understand how the skin may become a permissive microenvironment for the multiplication of this parasite, the expression of genes encoding to TLR-2, to the iNOS enzyme and to the cytokines IL-10, TNF-α and TGF-β was evaluated in skin of dogs naturally affected by CVL and were then was related to the parasite load of this tissue. We observed that the skin of dogs naturally affected by visceral leishmaniasis has a mixed Th1/Th2 immune response profile, with an increased expression of TLR-2, IL-10 and TNF-α that correlates to the increasing of the parasitic load in this tissue, giving these mediators an important role in the pathogenesis of CVL